2014
DOI: 10.3390/vaccines2030549
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Designing a Synthetic Tumor Vaccine: Multi-Component, Multivalency and Antigen Modification

Abstract: Synthetic tumor vaccines have been proven to be promising for cancer immunotherapy. However, the limitation of the specificity and efficiency of the synthetic tumor vaccines need further improvements. To overcome these difficulties, additional tumor-associated targets need to be identified, and optimized structural designs of vaccines need to be elaborated. In this review, we summarized the main strategies pursued in the design of synthetic tumor vaccines, such as multi-component, multivalency, antigen modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…It was found that, in preclinical study, anti‐Tn titers of Rha‐YAF‐Tn were higher when preimmunized with Rha‐OVA in mice, confirming the important role of the Rha in mediating the immune response . Li and co‐workers also synthesized several vaccine candidates containing MUC1 glycopeptides as the B‐cell epitopes, a T‐cell epitope peptide, and the Pam3CSK4 as TLR agonist . Recently, Guo and co‐workers synthesized a two‐component cancer vaccine candidate containing STn and αGalCer since αGalCer can play several roles such as liposomal carrier vehicle, activation of APCs, and Th epitope‐like function.…”
Section: Advances In Tacas Based Cancer Vaccinesmentioning
confidence: 94%
See 1 more Smart Citation
“…It was found that, in preclinical study, anti‐Tn titers of Rha‐YAF‐Tn were higher when preimmunized with Rha‐OVA in mice, confirming the important role of the Rha in mediating the immune response . Li and co‐workers also synthesized several vaccine candidates containing MUC1 glycopeptides as the B‐cell epitopes, a T‐cell epitope peptide, and the Pam3CSK4 as TLR agonist . Recently, Guo and co‐workers synthesized a two‐component cancer vaccine candidate containing STn and αGalCer since αGalCer can play several roles such as liposomal carrier vehicle, activation of APCs, and Th epitope‐like function.…”
Section: Advances In Tacas Based Cancer Vaccinesmentioning
confidence: 94%
“…132 Li and co-workers also synthesized several vaccine candidates containing MUC1 glycopeptides as the B-cell epitopes, a T-cell epitope peptide, and the Pam3CSK4 as TLR agonist. 133,134 Recently, Guo and co-workers 135…”
Section: Th Cell Epitope Is Another Common Component For Improving Thmentioning
confidence: 99%
“…Human MUC1 glycoproteins with abnormal O‐glycans have been found in high abundance on surfaces of epithelial tumor cells and have been investigated as potential candidates for antitumor vaccines. Prior investigations suggest that the presentation of MUC1 directly impacts immunogenicity, e.g., MUC1 fibrils led to effective B‐cell responses, while soluble monomeric MUC1 molecules exhibited little immunogenicity . Therefore, the effective molecule is MUC1 conjugated with an eleven residue long Q11 peptide, as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Despite encouraging results in some clinical trials, cancer vaccines are yet to have an impact on cancer [ 1 , 2 ]. Many strategies specific for a particular tumour associated antigen (TAA), including single or multiple peptides with or without ex vivo dendritic cells (DC) pulsing, DC targeting immunogens with or without adjuvants such as a toll-like receptor (TLR) agonist have been used [ 2 , 3 , 4 , 5 , 6 ]. To overcome some of the limitations of previous peptide vaccine strategies it is necessary to (1) incorporate both CD8 cytotoxic T cell (Tc) and CD4 T helper cell (Th) epitopes to promote the generation of long term immunity; (2) MHC restriction must be considered to allow application to the wider population and; (3) consideration to the most effective adjuvant to enhance immunogenicity [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%